HUBUNGAN ANTARA KONFORMITAS TERHADAP TEMAN SEBAYA DENGAN KENAKALAN REMAJA PADA SISWA USIA 13-15 TAHUN DI SMP NEGERI 1 CIWIDEY BANDUNG - Siti Fatimah (QUANTA, 2017)
The process of education is often hampered by the increased percentage of juvenile delinquency, whether it is committed in the school or at home that occurs because of the influence of peers. The population in this study is the students of class VIII in SMP Negeri 1 Ciwidey Bandung yang as many as 457 people. The sample was taken by using simple random sampling so there are 198 students selected. The data were collected using conformity scale and juvenile delinquency scale. Data analysis technique used is regression analysis and the value of correlation coefficient (R) obtained is of 0.297, the coefficient of determination (R2) = 0.088, F arithmetic = 18.905 and p = 0.000 which means that conformity correlated significantly to juvenile delinquency. While the conformity relationship to juvenile delinquency is determined by the value of R2 (coefficient of determination) of 0.088 that is equal to 8.8 percent of conformity associated with juvenile delinquency. The results showed that 72.2% (143 people) had a moderate conformity rate and 71.2% (141 people) had a moderate juvenile delinquency rate as well.